Extracellular Vesicles in Therapeutics: A Comprehensive Review on Applications, Challenges, and Clinical Progress - Jiyoung Goo; Yeji Lee; Jeongmin Lee; In-San Kim; Cherlhyun Jeong (MDPI AG, 2024)
Small Extracellular Vesicles (sEVs) are typically 30-150 nm in diameter, produced inside cells, and released into the extracellular space. These vesicles carry RNA, DNA, proteins, and lipids that reflect the characteristics of their parent cells, enabling communication between cells and the alteration of functions or differentiation of target cells. Owing to these properties, sEVs have recently gained attention as potential carriers for functional molecules and drug delivery tools. However, their use as a therapeutic platform faces limitations, such as challenges in mass production, purity issues, and the absence of established protocols and characterization methods. To overcome these, researchers are exploring the characterization and engineering of sEVs for various applications. This review discusses the origins of sEVs and their engineering for therapeutic effects, proposing areas needing intensive study. It covers the use of cell-derived sEVs in their natural state and in engineered forms for specific purposes. Additionally, the review details the sources of sEVs and their subsequent purification methods. It also outlines the potential of therapeutic sEVs and the requirements for successful clinical trials, including methods for large-scale production and purification. Finally, we discuss the progress of ongoing clinical trials and the implications for future healthcare, offering a comprehensive overview of the latest research in sEV applications.